2020
DOI: 10.21203/rs.3.rs-22444/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Piperaquine resistant Cambodian Plasmodium falciparum clinical isolates: in vitro genotypic and phenotypic characterization

Abstract: Abstract Background High rates of dihydroartemisinin-piperaquine (DHA-PPQ) treatment failures have been documented for uncomplicated Plasmodium falciparum in Cambodia. The genetic markers plasmepsin 2 ( pfpm2 ), exonuclease ( pfexo ) and chloroquine resistance transporter ( pfcrt ) genes are associated with PPQ resistance and are used for monitoring the prevalence of drug resistance and guiding malaria drug treatment policy.Methods To examine the relative contribution o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…1A). A pfexo E415G was e ciently installed onto the P. falciparum B5 background [24]. In parallel, a pfexo E415E transgenic line expressing wild-type E415 codon in the context of recodonization abating the Cas9 protospacer adjacent motif (PAM) site was also attempted to rule out a role for silent mutations in drug susceptibility.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1A). A pfexo E415G was e ciently installed onto the P. falciparum B5 background [24]. In parallel, a pfexo E415E transgenic line expressing wild-type E415 codon in the context of recodonization abating the Cas9 protospacer adjacent motif (PAM) site was also attempted to rule out a role for silent mutations in drug susceptibility.…”
Section: Resultsmentioning
confidence: 99%
“…CRISPR/Cas9 approaches have transformed the speed and scale with which Plasmodium genome editing can be achieved, and the approach has been employed to introduce point mutations into several P. falciparum genes [53]. In this study, instead of using P. falciparum 3D7 or Dd2 lines, the Cambodia adapted-B5 line [24] was employed with the hypothesis that the B5 line has a close genetic background to the currently circulating P. falciparum in Cambodia where both ART-and PPQ-resistance parasites have been detected. It has been previously shown that different phenotypes were observed when using different parasite backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations